Evaluation of CD4/CD8 ratio in children with immune thrombocytopenic purpura (ITP) after treatment with intravenous immunoglobulin (IVIG): Effect of IVIG on CD4/CD8 ratio in pediatric patients with ITP - Zhang, Wenming; Qian, Xiaodan; Chen, Wei (Cellular and Molecular Biology, 2022)
Intra Venous Immunoglobulin (IVIG) is a plasma-derived product used to treat many autoimmune diseases, including thrombocytopenia, immunodeficiency, and infectious diseases. In this study, the effect of IVIG injection was evaluated on the number of white blood cells, neutrophils, lymphocytes, and platelets. The effect of IVIG was also considered on the percentage of CD4 and CD8 positive cells T cell lymphocytes and their absolute number in pediatric patients with immune thrombocytopenic purpura. The study was a cross-sectional study performed on 32 patients with ITP. In these patients, a blood sample was taken before and one hour after the start of the IVG injection. For all samples, a complete blood cell, platelet count, and differential blood leukocyte count were performed by Sysmex kx-21. Then labeled anti-CD4 and anti-CD8 markers were used to evaluate the type of lymphocytes. SPSS software version 15 and a t-test with a significant level of p <0.05 were used for statistical analysis of the obtained results. Pearson correlation coefficient was also used to evaluate the relationship between patients’ age and the total volume of injected IVIG results. Examination of blood cell counts showed a significant decrease in the mean of white blood cells, neutrophils, and lymphocytes after intravenous immunoglobulin injection. However, these changes were not statistically significant for platelets. A comparison of the mean percentage of CD4 and CD8 cells shows a significant increase in the CD4 / CD8 cell ratio after injection. The absolute number of CD4 and CD8 lymphocytes one hour after IVIG injection was significantly decreased, but their proportion increased after injection. Generally, IVIG reduces the absolute number of neutrophils, but this reduction is not associated with infection problems. This decrease is also seen in the number of lymphocytes. However, the change in the number and percentage of CD4 and CD8 cells depends on the sampling time following IVIG injection.